Metabolic power: A step in the right direction for team sports - Polglaze, T.; Hoppe, M. W. (International Journal of Sports Physiology and Performance, 2019)
The ability of the "metabolic power" model to assess the demands of team-sport activity has been the subject of some interest—and much controversy—in team-sport research. Because the cost of acceleration depends on the initial speed and the costs of acceleration and deceleration are not "equal and opposite," changes in speed must be accounted for when evaluating variable-speed locomotion. The purpose of this commentary is to address some of the misconceptions regarding "metabolic power," acknowledge its limitations, and highlight some of the benefits that energetic analysis offers over alternative approaches to quantifying the demands of team sports.